Cephalometric Analysis for Gender Determination Using Maxillary Sinus Index: A Novel Dimension in Personal Identification - Tanya Khaitan; Arpita Kabiraj; Uday Ginjupally; Ritika Jain (Hindawi Limited, 2017)
Purpose. Radiography is important in forensic odontology for the identification of humans. The maxillary sinus is the largest of the paranasal sinuses and first to develop. Sinus radiography has been used for identification of skeletal remains and determination of gender. Hence, the aim and objectives of the present study were to establish a new method for gender determination using maxillary sinus index from lateral cephalometric radiographs and to establish the reliability of maxillary sinus for gender determination. Methods. A total of 50 adult digital lateral cephalometric radiographs (25 males and 25 females) were included in the study. The maxillary sinus analysis was performed on these radiographs using the height and width measurement tools of Sidexis XG software. Maxillary sinus index was calculated, discriminant function analysis performed, and discriminant equation derived for determination of gender. Results. The mean maxillary sinus height and width were found to be higher in males, whereas the maxillary sinus index was greater in females. The discriminant function analysis derived in the study was able to differentiate the sex groups with sensitivity of 68% and specificity of 76%. Conclusions. From the results of the present study, it may be concluded that morphometric analysis of maxillary sinus can be used as a reliable tool in gender determination.